An Ultra-High Speed Whole Slide Image Viewing System - Yukako Yagi; Shigeatsu Yoshioka; Hiroshi Kyusojin; Maristela Onozato; Yoichi Mizutani; Kiyoshi Osato; Hiroaki Yada; Eugene J. Mark; Matthew P. Frosch; David N. Louis (Analytical Cellular Pathology)
Background: One of the goals for a Whole Slide Imaging (WSI) system is implementation in the clinical practice of pathology. One of the unresolved problems in accomplishing this goal is the speed of the entire process, i.e., from viewing the slides through making the final diagnosis. Most users are not satisfied with the correct viewing speeds of available systems. We have evaluated a new WSI viewing station and tool that focuses on speed.